2013
DOI: 10.1016/j.bbmt.2012.12.011
|View full text |Cite
|
Sign up to set email alerts
|

PreImplantation Factor Reduces Graft-versus-Host Disease by Regulating Immune Response and Lowering Oxidative Stress (Murine Model)

Abstract: Bone marrow transplantation (BMT) to treat severe hematologic malignancies often leads to potentially fatal acute graft-versus-host disease (GVHD), despite attempts at better donor-recipient matching and/or use of immunosuppressive agents. We report that embryo-derived PreImplantation Factor (PIF) plays a determining role in developing maternal/host tolerance toward the semiallogeneic or total allogeneic embryo and in regulating systemic immune response. Synthetic PIF treatment has proven effective in preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 35 publications
8
63
0
Order By: Relevance
“…Proteomic analysis of the pancreas demonstrated that the ranking proteins which were up-regulated are the PDI and HSP family members. Further, both the neuroinflammation and GVHD models demonstrated that the highest ranking pathway/mechanism of PIF-induced protection was against oxidative stress and protein misfolding [27], [28], [30], [31], [44] [45], [46] [47]. Thus fundamental mechanisms through which PIF operates in the embryo are clearly translatable for non-pregnant immune disorder models.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic analysis of the pancreas demonstrated that the ranking proteins which were up-regulated are the PDI and HSP family members. Further, both the neuroinflammation and GVHD models demonstrated that the highest ranking pathway/mechanism of PIF-induced protection was against oxidative stress and protein misfolding [27], [28], [30], [31], [44] [45], [46] [47]. Thus fundamental mechanisms through which PIF operates in the embryo are clearly translatable for non-pregnant immune disorder models.…”
Section: Discussionmentioning
confidence: 99%
“…These are in line with observations made in non-pregnant in vivo models. Specifically, in several models of immunity and transplant, PIF led to protection against oxidative stress (Weiss et al, 2011(Weiss et al, , 2012Azar et al, 2013;Shainer et al, 2013;Almogi-Hazan et al, 2014;Mueller et al, 2014Mueller et al, , 2015. In addition, as recently shown, PIF also protects against ionized radiation-induced damage (Shainer et al, 2014).…”
Section: Third Critical Element In Pregnancy Success; Immune Responsementioning
confidence: 88%
“…This folding structure has to be maintained to be biologically active since the scrambled PIF (same aminoacids but in random order) does not replicate PIF effect, bioinfromatics, in vitro ( Fig. 1) (Barnea et al, 2012b;, as well as in vivo (Weiss et al, 2011;Azar et al, 2013). Based on recent data PIF targets Kv1.3␤-cortisone target (Paidas et al, 2010;.…”
Section: Introductionmentioning
confidence: 95%
“…Additionally, the angiotensin family (1–7) increases neuronal voltage-gated potassium current through nitric oxide pathway [14,56]. Furthermore, viral infections cause, in the prenatal period, activation of the inOS pathway in murine models [57]. We demonstrated that PIF controls the inflammatory response in macrophages by blocking this specific pathway [58].…”
Section: Discussionmentioning
confidence: 99%